Modelling flood map during Alex hurricane: Simulation enforced by multisensory precipitation in the city of Monterrey, Mexico - Stella, Juan M. (Tecnología y ciencias del agua, 2025)
Alex hurricane was one of the most intense tropical cyclones in the North Atlantic that caused fatalities and loses in the Northeast of Mexico due to the flash floods. Flood hazard mapping is a vital tool to assess inundation areas, which can be simulated using hydraulic and hydrologic models. This study describes the modelling of a flood event during Alex hurricane in the Santa Catarina River Watershed, Northeast of Mexico, applying HEC-HMS and two dimensional (2D) HEC-RAS models forced with Multi Radar Multi Sensor-Quantitative Precipitation Estimation (MRMS-QPE). A HEC-HMS model was developed forced by (MRMS-QPE) as input to simulate discharges along the Santa Catarina River. The simulated discharges were introduced as border conditions along the mainstream of the Santa Catarina River inside a HEC-RAS 2D model to simulate a flood map along the mainstream of the Santa Catrina River. The observed against the simulated peak discharges achieved a r2 of 0.97 and a Nash-Sutcliffe coefficient of 0.97. The observed against the simulated accumulated discharges achieved a r2 of 0.99 and a Nash-Sutcliffe coefficient of 1.0. The observed against the simulated stages achieved a r2 of 0.74 and, a Nash-Sutcliffe coefficient of 0.68. The use of HEC-HMS and HEC-RAS 2D models coupled with MRMS-QPE shows that these models are user friendly to setup, the model has stability and the capacity to simulate flood maps along the whole mainstream of the Santa Catarina River with good results.